Bacterial Infections Transmitted by Ticks in Barnaul: Epidemiological and Epizootological Situation, Diagnostic Problems - T. A. Chekanova; A V. Rakov; K. Petremgvdlishvili; A. V. Timonin; N. V. Lukyanenko; T. V. Safyanova; S. V. Shirokostup; N. Ya. Lukyanenko; U. V. Kalinina; I. G. Pashchenko; Т. А. Чеканова; А. В. Раков; et al. (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2024)
Relevance. The Altai Кray with its administrative center, Barnaul, is an endemic region for tick–borne rickettsioses. The contribution of other tick-borne infections (TBI) to the structure of overall morbidity in the subject is significantly lower. To assess the risks of complication of the epidemiological situation for bacterial TBI (tick-borne rickettsioses, borrelioses, human granolucytic anaplasmoses, human monocytic ehrlichiosis, coxiellosis) and understand the level of their diagnosis in the region, it is important to study the occurrence of their pathogens in ticks, comparing them with the officially registered incidence. The aim is the study of the epidemiological and epizootological situation in Barnaul for bacterial tick-borne infections as well as an analysis of the factors influencing the registration of the incidence of these infections. Materials and methods. The materials were official statistical reporting data, information, analytical materials, accounting and reporting documentation of the Department of Rospotrebnadzor and the Ministry of Health of the Altai Region. The infection of ticks collected in the biotopes of Barnaul with different landscapes by pathogens of tick-borne encephalitis, human granulocytic anaplasmosis (HGA), human monocytic ehrlichiosis (HME), borrelioses, rickettsioses, and Q fever were studied using molecular biological methods. The species of Rickettsia were determined by Sanger sequencing followed by phylogenetic analysis. Results. Rickettsia conorii subsp. raoultii detected in the Dermacentor ticks with a high occurrence (61.9%), DNA of R. helvetica detected in the Ixodes ticks (5.1%). R. sibirica was not been detected. The infection rate of ticks by Borrelia burgdoferi s.l. was 27.8%; 5.1% of imagos contained B. miyamotoi DNA. Pathogens of HGA, HME were founded in 6.2%, 1.0% of individuals of Ixodes ticks, respectively. In two copies out of 300, the causative agent of Q fever identified. The dynamics of the number of people affected by tick bite over the period ...